Bioactivities of isolated phytochemical constituents and extracts of crateva adansonii. - Vinujan, S.; Saravanan, V.; Pholtan, R. (Journal of Amasya University the Institute of Sciences and Technology, 2021)
Crateva adansonii DC. is a tree belonging to the Capparaceae family. In traditional medicine, it is used to cure several disorders including constipation, earache, fevers, itch, malaria, rheumatic pains, and snakebites. Furthermore, phytochemicals including daucosterol, phytol, pyropheophorbide A, suramin, and ψ-taraxasterol have been isolated from different parts of C. adansonii. This review paper objects to scrutinize, recap, and document the reported bioactivity studies of C. adansonii. ScienceDirect, Web of Science, Semantic Scholar, Scopus, and PubMed were utilized to detect the applicable published works from 1900 to June 2021. Up to now, in vivo and in vitro scientific evidence is available for various bioactivities. In addition, analgesic, antiarthritic, antibacterial, anticancer, antifungal, antiinflammatory, antimalarial, antioxidant, and antiprotozoal activities have been observed for various parts of this plant. This work supports a detail information related to this plant for further studies in the future.
Keywords: Capparaceae; Crateva adansonii; Ethnobotany; Siddha Medicine; Sri Lanka